Minute larvae of Leptotyphlinae (Coleoptera: Staphylinidae): description of three genera with discussion on the monophyly and phylogenetic position of the subfamily as inferred from larval morphology - Grebennikov, Vasily V.; Newton, Alfred F. (Zootaxa, 2008)
External morphology of larvae belonging to three unidentified genera of the rove-beetle subfamily Leptotyphlinae (Coleoptera: Staphylinidae) collected in Mexico, Chile and Australia, respectively, is described and illustrated. Larvae of Leptotyphlinae can be distinguished from all other Staphylinoidea larvae by the combination of their small size (maximum documented head width 0.128 mm), along with complete absence of eyes, lyriform frontal ecdysial lines, long coronal suture extending for about 40% of head length, short antennae not longer than 1/3 of head length, non-serrate mandibles with a single pre-apical tooth, tibiotarsi swollen in middle with two ventral spines, and indistinctly articulated short urogomphi not longer than twice their basal width. At least some of these characters are likely to support monophyly of the subfamily. Leptotyphlinae are hypothesized to belong to the Staphylinine Group of subfamilies sharing with at least some of them the following larval characters: labrum fully fused with clypeus; posterior tentorial arms extremely thin, thread-like and more than 20 times longer than wide; posterior tentorial pits short, rounded to elongate; cardo lacking transverse sclerotized ridge. The sister-group relationships of Leptotyphlinae to a clade of Pseudopsinae+Paederinae+Staphylininae is hypothesized with the following larval characters in support: lyriform frontal arms; each maxilla articulated laterally to head capsule by a condyle; maxillary mala parallel-sided (=finger-shaped) and articulated to stipes. A larval identification key to all three presently described genera is given.